1998
DOI: 10.1021/jf970579t
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Four Commonly Used Pesticides in Malaysian Agricultural Soils

Abstract: First-order kinetics were observed for the degradation of 2,4-D, lindane, paraquat, and glyphosate in sandy loam and muck soils, with the exception of glyphosate degradation in an anaerobic muck. Short half-lives were observed for 2,4-D in aerobic (3.4 days) and anaerobic (9.3 days) muck soils, while longer half-lives were found for glyphosate (19.2 days) and 2,4-D (35.9 days) in the sandy loam. Long half-lives were observed for lindane (1.0−1.7 years) and paraquat (1.4−7.2 years) in the soils. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
13
1
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 28 publications
10
13
1
6
Order By: Relevance
“…The amounts of 14 C-non-extractable residues, which are the slow released residues because they depend on the microbial attack on the soil fraction where they are bound, varied from 19% (four applications, two months) to 29.5% (three applications, two months). Finally, the balance of total radiocarbon recovered from 14 C-glyphosate varied from 80% to 103% (Figure 3), which is in agreement with Cheah et al (1998).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The amounts of 14 C-non-extractable residues, which are the slow released residues because they depend on the microbial attack on the soil fraction where they are bound, varied from 19% (four applications, two months) to 29.5% (three applications, two months). Finally, the balance of total radiocarbon recovered from 14 C-glyphosate varied from 80% to 103% (Figure 3), which is in agreement with Cheah et al (1998).…”
Section: Resultssupporting
confidence: 83%
“…The amount of 14 CO 2 varied from approximately 47% (one application) to 33.5% (four applications), two months after treatments. These values are higher than those detected by Cheah et al (1998). Araújo et al (2003) found higher production of carbon dioxide from soils treated six years with glyphosate than from soils treated only one time.…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…de até 22,7 anos para solos vulcânicos, com elevado grau de sorção (Nomura & Hilton, 1977) e t 1/2 em torno de 19 dias (Cheah et al, 1998) para a maioria dos solos. Apesar do glifosato ser uma molécula bastante rica em energia, e constituída de C, H, O, P e N, o que a torna altamente biodegradável em meio líquido sem adsorventes.…”
Section: Transformação Biótica -Biodegradaçãounclassified